Prostitution and White Slave Trafficking: The International Discourse of Victimhood (Chile, 1934 [Prostitución y Trata de Blancas: El Discurso Internacional del Victimismo (Chile, 1934 - Gálvez-Comandini, A (Universidade do Vale do Rio dos Sinos, 2018)
This article seeks to describe and analyze how the association between the trafficking of white women and prostitution was established and reproduced in Chile, in a way similar to how the discourse was expanding internationally, with a marked direction from Europe to America, where well-defined profiles of the subjects involved in that crime were constructed: the foreign pimp or pander and the prostitute who is a victim of tricks and sexual exploitation far from her native country. The case of Chile is particularly attractive, as this country, unlike what happened on the Latin American Atlantic coast, had not received a large contingent of European immigrants to justify that this kind of discourse was so successful among local authorities and the population in general. Through the study of an indictment for white slave trafficking filed in 1934 against an Italian subject residing in Santiago de Chile, we will reconstruct at the national and international level the scenarios and contexts that allowed this type of ideas to permeate the interpretation of the local reality, which, as we will see, was far from what the victimizing paradigm of white slave trafficking tried to define as a cross-border crime. © 2018 Universidade do Vale do Rio dos Sinos. All rights reserved.